Photoshop elements 2019 for dummies - Obermeier, Barbara; Padova, Ted (--For dummies., 2019)
"Take your photos from dull to dazzling! Photoshop Elements gives amateur photographers the tools to fix, enhance, and improve their photos, and then to create works of art. With so much power at hand, you'll appreciate how this easy-to-use guide saves you time and frustration by walking you through all the things you can do to improve your digital images! Discover what you need to know to navigate the interface, correct color, adjust contrast, enhance brightness, and use filters to add artistic effects. Inside: find one-click photo fixes; organize your images; make your photos look better; work with Photoshop layers; apply special art effects; experiment with filters; use the cataloguing tools; create a movie with your images."--Back cover